Poly(acrylonitrile) ultrafiltration membranes. II. membrane morphology and permeation characteristics - Phadke, M. A.; Kulkarni, Sudhir S.; Karode, Sandeep K.; Musale, D. A. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The rheology and phase-boundary characteristics of various solutions comprising three polyacrylonitrile (PAN) grades dissolved in solutions of N,N-dimethylformamide + salt (LiCl, ZnCl2, or AICl(3)) additives were correlated with the resulting membrane morphology as determined by microscopy and permeability measurements. The phase separation characteristics of the dope solution were not markedly affected by the PAN molecular weight (MW); however, they were affected by the salt additive. For higher MW grades, the effect of salt addition can also be masked by the increased self-association tendency of the polymer chains. PAN-B and -C membranes were clearly less asymmetric in structure than the lower MW PAN-Abased membranes. This is attributed to the higher viscosity/lower diffusivity of the PAN-13 and -C solutions, which results in slower solvent-nonsolvent exchange during the phase inversion process. Two factors reduce the incidence of surface defects (increased bubble points): (a) higher solution viscosity dampens surface perturbations during phase inversion, and (b) phase inversion pathways resulting in more homogenous morphology lead to membranes with higher bubble points. (c) 2005 Wiley Periodicals, Inc.
Keywords: bubble point; membranes; Morphology; phase inversion; salts; viscosity

Stereoselectivity ratios in a simple Diels-Alder reaction in aqueous salt solutions of alcohols - Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron, 2005)
This is the first exhaustive report on the variation of stereoselectivity ratios for a simple Diels-Alder reaction between cyclopentadiene and methyl acrylate. The reaction was carried out in aqueous mixtures of methanol, ethanol, propan-1-ol and butan-1-ol in presence of LiClO4, LiCl, NaCl, KCl, CaCl2 and MgCl2. The endo sterecisomer decreases with the increase in carbon chain length of the alcohol. However, LiClO4, a salting-in agent in water becomes salting-out in aqueous mixtures of alcohols. The solvent properties, thus can be attuned by adjusting the amount of solvents and salts. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: aqueous alcohols; Diels-Alder reaction; endolexo ratios; salts

Mixed-stack charge transfer crystals of pillar[5]quinone and tetrathiafulvalene exhibiting ferroelectric features - Shivakumar, Kilingaru I.; Swathi, Kadaba; Goudappagouda; Das, Tamal C.; Kumar, Ashwani; Makde, Ravindra D.; Vanka, Kumar; Narayan, Kavassery S.; Babu, Sukumaran Santhosh; Sanjayan, Gangadhar J. (Chemistry- A European Journal, 2017)
Ferroelectric materials find extensive applications in the fabrication of compact memory devices and ultra-sensitive multifunctional detectors. Face-to-face alternate stacking of electron donors and acceptors effectuate long-range unidirectional ordering of charge-transfer (CT) dipoles, promising tunable ferroelectricity. Herein we report a new TTF-quinone system-an emerald green CT complex consisting pillar[5]quinone (P5Q) and tetrathiafulvalene (TTF). The CT crystals, as determined by single crystal synchrotron X-ray diffraction, adopt a 1:1 mixed-stack arrangement of donor and acceptor with alternating dimers of TTF and 1,4-dioxane encapsulated P5Q. The TTF-P5Q.dioxane crystal possesses a macroscopic polarization axis giving rise to ferroelectricity at room temperature. The CT complex manifests ferroelectric features such as optical polarization rotation, temperature-dependent phase transition and piezoelectric response in single crystals. Ferroelectric behavior observed in P5Q-based CT complex widens the scope for further work on this structurally intriguing and readily accessible cyclic pentaquinone.
Keywords: Acceptor; Charge-transfer complexes; Chemistry; Conductors; DDQ; Donor; ferroelectric; Macrocycles; Organic Metals; Pi-interaction; Pillar[5]quinone; salts; Transfer Complexes; Transport

Effect of CaCl2 and ZnCl2 salts on isobaric vapor-liquid equilibrium in separation of the azeotropic mixture of ethanol plus water - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Fluid Phase Equilibria, 2021)
Present work analyzes potential of calcium chloride (CaCl2) and zinc chloride (ZaCl(2)) salts as entrainer for breaking the minimum boiling azeotrope of ethanol and water. Isobaric vapor-liquid equilibrium (VLE) data for the binary systems of water + ethanol and ternary system of water + ethanol + calcium chloride, and water + ethanol + zinc chloride were measured at a constant pressure of 94.5 kPa. The effect of salts on the relative volatility of ethanol to water as well as on the vapor phase mole fractions of ethanol were also studied experimentally. From the experimental results, it is observed that with addition of salts, the azeotropic point of the ethanol and water system can be eliminated. Salting out effects in case of calcium chloride was more than that zinc chloride salt. The results obtained in this work showed that calcium chloride could be a better choice for separation of the water + ethanol azeotrope. Electrolyte nonrandom two-liquid (eNRTL) model was used to correlate the experimental VLE data. The model prediction with the regressed parameters was found in well agreement with the experimental data. The experimental data obtained in this work was found thermodynamically consistent using van Ness test. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Azeotrope; eNRTL; Ethanol; salts; Vapor-liquid equilibrium; Water